2015
DOI: 10.1353/jda.2015.0046
|View full text |Cite
|
Sign up to set email alerts
|

Malaysian Fast Food Brand Equity

Abstract: Most Malaysian research defines the brand equity dimensions. This paper addresses this gap by developing an empirical research model with better understanding of sequential relationships between the dimensions of brand equity within the Malaysian fast food context. The results indicate perceived quality (PQ) and brand awareness (BA) are the initial stage of brand building. Brand familiarity, brand image, and brand trust serve as important role in enlightening the relationships between PQ, BA, and attitudinal b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 78 publications
1
1
0
Order By: Relevance
“…Confirmation of this also came from earlier studies by Chow & Holden (1997) and Heskett et al (1994) who determined that increasing the percentage of loyal customers by as little as 5% can increase profitability by as much as 30% to 85%. This was also consistent with Tan et al (2015) who stated that in the initial stages of brand building, brand awareness played a crucial role. Therefore, from the above and other research the following observed variables were included in the study.…”
Section: Staff Service Quality (Sq)supporting
confidence: 90%
“…Confirmation of this also came from earlier studies by Chow & Holden (1997) and Heskett et al (1994) who determined that increasing the percentage of loyal customers by as little as 5% can increase profitability by as much as 30% to 85%. This was also consistent with Tan et al (2015) who stated that in the initial stages of brand building, brand awareness played a crucial role. Therefore, from the above and other research the following observed variables were included in the study.…”
Section: Staff Service Quality (Sq)supporting
confidence: 90%
“…In this sphere of study, CBBE measurement has received less scholarly attention (Kim and Kim, 2004; Majid and Chik, 2014; Nam et al , 2011), as the majority of studies have focused on very specific establishment types such as restaurant chains (Hyun and Kim, 2011), ethnic restaurants (Lu et al , 2015) or fast-food establishments (Tan et al , 2015). By contrast, the present research addresses the CBBE formation process of full-service restaurants.…”
Section: Literature Reviewmentioning
confidence: 99%